Developmental Indicators of School-Age Children, Living in the Regions with Iodine Deficiency - T.V. Sorokman (Zaslavsky O.Yu., 2015)
The article provides the results of studying developmental indicators of children living in the areas of iodine deficiency. The basic anthropometric parameters (height and weight, chest circumference) were defined, the estimation of intellectual development in 819 children aged 7-16 years living in the regions with mild (472 persons) and moderate (347 persons) iodine deficiency was carried out. Examined children were standardized by major factors of developmental effect. Anthropometric measurements were carried out by standard methods. Maturity of intellectual functioning was determined using the fragment of R. Cattell test, indicators of mental activity - with proofreading test in conjunction with reading rate test. In all children we have carried out measurement of daily ioduria (Sandell - Kolthoff reaction), palpation of the thyroid gland, determination of its size and structure using ultrasound. It was found that the diet of children is characterized by deficiency of food rich in iodine. Iodized salt was used only by 1 of 50 families. Children living in the regions with moderate iodine deficiency in all age subgroups have lower rates of physical development. A third of children living in areas of iodine deficiency have disharmonic physical development. 13.8 % of children from the regions of iodine deficiency have changes in the majority of the studied cognitive functions. Leading disabilities in the whole group of children were memory impairment and fine motor skills disorders. The level of intellectual maturity, productivity and accuracy of human performance decreases with growing iodine deficiency.